2016
DOI: 10.2135/cropsci2015.06.0347
|View full text |Cite
|
Sign up to set email alerts
|

Can Frequent Measurement of Normalized Difference Vegetative Index and Soil Nitrate Guide Nitrogen Fertilization of Kentucky Bluegrass Sod?

Abstract: Objective approaches to guide N fertilization of turfgrass sod crops are lacking. This study was conducted to determine the relationships among normalized difference vegetative index (NDVI), frequently‐measured soil NO3–N concentrations, and peak‐shear force of predominately Kentucky bluegrass (Poa pratensis L.) sod, and to evaluate if those relationships could help guide N fertilization. Ramp calibration strips (RCS) with varying N rates were established within production sod fields in Rhode Island across thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…However, the use of multiple color parameters (L*C*h°) gave higher R 2 values (0.69) in the current study. On the other hand, in studies using hand-held NDVI devices, different results have been reported for the prediction of nitrogen content depending on the type of turfgrass and NDVI devices (R 2 =0.19-0.85) (Frank, 2008;Moss and Bell, 2010;Caturegli et al, 2016;Guillard et al, 2016;Inguagiato and Guillard, 2016). In the present study, similar coefficient of determination (R 2 ) value between NDVI and N content was determined (0.73) ( Table 4).…”
Section: Results Of Regression Analysissupporting
confidence: 53%
“…However, the use of multiple color parameters (L*C*h°) gave higher R 2 values (0.69) in the current study. On the other hand, in studies using hand-held NDVI devices, different results have been reported for the prediction of nitrogen content depending on the type of turfgrass and NDVI devices (R 2 =0.19-0.85) (Frank, 2008;Moss and Bell, 2010;Caturegli et al, 2016;Guillard et al, 2016;Inguagiato and Guillard, 2016). In the present study, similar coefficient of determination (R 2 ) value between NDVI and N content was determined (0.73) ( Table 4).…”
Section: Results Of Regression Analysissupporting
confidence: 53%
“…Spectral reflectance is measured with given wavelengths of light, and studies (Trenholm et al, 1999 ; Bell et al, 2002 ; Fitz–Rodríguez and Choi, 2002 ; Keskin et al, 2008 ) have shown that spectral reflectance could be well correlated with visual quality for turfgrass species maintained under different management practices. Spectral reflectance is sensitive to N fertilization of turfgrasses (Caturegli et al, 2016 ; Guillard et al, 2016 ) and therefore has the potential to serve as an objective measurement of turfgrass performance. For example, spectral reflectance has been used to detect chlorophyll concentration and has also been shown to have a good correlation with plant N status (Horler et al, 1983 ; Steven and Clark, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to turfgrass lawns, using spectral reflectance to guide N fertilization is applicable to other turf uses such as athletic fields, golf (Baldwin & Brede, 2011; Inguagiato & Guillard, 2016; Kruse, Christians, & Chaplin, 2006; López‐Bellido et al., 2012; Zhu, Schlossberg, Bryant, & Schmidt, 2012), or sod production (Guillard et al., 2016; Li, Fang, & Han, 2011). Because fertilization is more frequent in these systems than lawns, the frequency of reflectance readings will need to be increased to match the fertilizer applications.…”
Section: Discussionmentioning
confidence: 99%
“…A commonly used spectral measurement in turfgrass research to determine treatment differences is the normalized difference vegetative index (NDVI). There are numerous citations in the turfgrass literature reporting significant relationships between NDVI or other spectral‐reflectance signals with N fertilization (reviewed in Bell, Kruse, & Krum, 2013; Catureglia et al., 2015, 2016; Caturegli et al., 2020; Geng, Guillard, Mangiafico, & Morris, 2014; Geng, Guillard, & Morris, 2014; Guillard, Fitzpatrick, & Burdett, 2016; Inguagiato & Guillard, 2016; Moore et al., 2019; Moore, Guillard, Morris, & Brinton, 2019; Obear, Kreuser, Hubbard, DeBels, & Soldat, 2017). However, relationships between reflectance signals and the response of turfgrass to N fertilization have not been analyzed with the objective to create site‐specific fertilizer recommendations.…”
Section: Introductionmentioning
confidence: 99%